2015
DOI: 10.2134/agronj15.0212
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Rhizobia and Biochar on Growth and Physiology of Maize

Abstract: This experiment aimed to evaluate plant growth promoting rhizobia in combination with biochar for improving the growth and physiology of maize (Zea mays L.). Three rhizobia isolated from different legumes (RH1, RH2, and RH3) were used to inoculate maize growing in soil amended with different levels of biochar (0.0, 0.5, 1.0, and 1.5%) under controlled conditions. The magnitude of improvement in the growth and physiology of maize varied due to rhizobial inoculation and application of biochar, either alone or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…Our study showed that suitable amounts of biochar (0.2%-1%) promoted the growth and development of aboveground and underground organs of tobacco, while higher amounts of biochar (5%) inhibited the shoot growth but promoted the root growth of tobacco. A study about the effect of biochar on maize growth and development also led to the similar conclusion that, the growth and physiology of maize was improved at 1.0% biochar level as compared to other biochar levels (0.5 and 1.5%) (Ahmad et al, 2015). And a substantial increase was found in plant height, shoot dry weight and maize yield with biochar addition compared to the untreated control (Abid et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…Our study showed that suitable amounts of biochar (0.2%-1%) promoted the growth and development of aboveground and underground organs of tobacco, while higher amounts of biochar (5%) inhibited the shoot growth but promoted the root growth of tobacco. A study about the effect of biochar on maize growth and development also led to the similar conclusion that, the growth and physiology of maize was improved at 1.0% biochar level as compared to other biochar levels (0.5 and 1.5%) (Ahmad et al, 2015). And a substantial increase was found in plant height, shoot dry weight and maize yield with biochar addition compared to the untreated control (Abid et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…This is indicative of the synergistic effect of biochar when applied with fertilizer sources. Such a synergistic effect has been reported in various studies such as for the increased production of maize by Yamato et al [29] through combined biochar and fertilizer; Yamato et al reported a 4-12 times higher yield of rice and sorghum when combined with fertilizer and compost [14,30] and reported increases in corn yield through increased P availability and uptake when biochar combined with arbuscular mycorrhiza (AM) fungal spores [31,32].…”
Section: Corn Dry Matter Yieldmentioning
confidence: 90%
“…further stimulated this effect. Synergy between biochar and various rhizobial strains has also been reported to improve plant growth under normal conditions . This positive impact of biochar might be due to its ability to enhance nutrient‐ and water‐holding capacity, making soil conditions more conducive to plant growth .…”
Section: Discussionmentioning
confidence: 99%
“…Synergy between biochar and various rhizobial strains has also been reported to improve plant growth under normal conditions. 44 This positive impact of biochar might be due to its ability to enhance nutrientand water-holding capacity, making soil conditions more conducive to plant growth. 45 Rizwan et al 16 critically reviewed the impact of biochar on plant growth and soil properties under stress.…”
Section: Discussionmentioning
confidence: 99%